A Single Clinical Case report on Management of Infected Sebaceous Cyst through Ayurvedic Surgical intervention vis-à-vis Chedhana, Visravana and Seevana Karma - P K M, Poornima; C P, Vineeth; D, Ganavi; B C, Mallanagouda; Gowda, Vivek; B, Navyashree; K M, Anil Kumar; Kumar B G, Chethan (Journal of Neonatal Surgery, 2025)
A sebaceous cyst is a very common type of slow-growing, non-cancerous elevation beneath the skin. It is a retention cyst lined with true stratified squamous epithelium derived from hair follicle. It is due to blockage of the duct of sebaceous gland, causing a cystic swelling. Sebaceous glands are situated in dermis which secretes sebum through sebaceous duct which opens either directly to skin surface or in to a hair follicle. Patients have a more cosmetic concerns than morbidity and mortality. It appears smooth to touch, varies in size, and is generally round in shape. They are most commonly found on the face, scalp and scrotum and in hairy areas. It is not seen in palms and soles as there are no sebaceous glands. In cases of long duration, they could result in hair loss on the skin surface that is immediately above the cyst. Everyone seeks medical care due to cosmetic reasons. There are no medicines yet other than surgical removal. In Ayurveda, sebaceous cysts can correlate with the Kaphaja Granthi based on characteristic similarities1. Here we present a case of sebaceous cyst with mild pain in back of right shoulder (under the scapular region) where Chedhana and Seevana karma is done according to Ayurveda line of treatment